2011
DOI: 10.1603/ec10391
|View full text |Cite
|
Sign up to set email alerts
|

The A2′N Mutation of the RDL γ-Aminobutyric Acid Receptor Conferring Fipronil Resistance in Laodelphax striatellus (Hemiptera: Delphacidae)

Abstract: The planthopper Laodelphax striatellus (Fallén) (Hemiptera: Delphacidae) is a serious insect pest of rice, Oryza sativa L., and has developed resistance to fipronil in Japan. Sequence analysis of L. striatellus RDL gamma-aminobutyric acid (GABA) receptor subunit (LS-RDL) genes from a fipronil-resistant population and a fipronil-susceptible strain identified the A2'N mutation (index number for M2 membrane-spanning region), that was previously implicated in fipronil resistance in the planthopper Sogatella furcif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 37 publications
2
64
0
Order By: Relevance
“…SF-RDL genes To co-express wild-type and mutant SF-RDL genes, the plasmid pENTR-pA-pAc 21) was used. The plasmid pENTR1A-Sf-RDL was digested with BamHI and Not I, and the BamHINot I fragment containing the wild-type SF-RDL gene was inserted into the BamHI-Not I site of pENTR-pA-pAc; the resulting plasmid was designated as pENTR pA-pAc-Sf-RDL.…”
Section: Construction Of Vectors To Co-express Wild-type and Mutantmentioning
confidence: 99%
See 2 more Smart Citations
“…SF-RDL genes To co-express wild-type and mutant SF-RDL genes, the plasmid pENTR-pA-pAc 21) was used. The plasmid pENTR1A-Sf-RDL was digested with BamHI and Not I, and the BamHINot I fragment containing the wild-type SF-RDL gene was inserted into the BamHI-Not I site of pENTR-pA-pAc; the resulting plasmid was designated as pENTR pA-pAc-Sf-RDL.…”
Section: Construction Of Vectors To Co-express Wild-type and Mutantmentioning
confidence: 99%
“…[16][17][18][19] In a previous study, the A2′N mutation was associated with fipronil resistance and was suggested to be a heterozygous mutation in S. furcifera 20) and L. striatellus. 21) A membrane potential assay showed that the A2′N mutation in the L. striatellus RDL GABA receptor subunit (LS-RDL) confers fipronil resistance in the heterozygous expression of wild-type and A2′N mutant LS-RDL genes. 21) In this study, we used heterozygous expression and heterozygous receptors to indicate GABA receptors expressed on co-transfected cells with an equal amount of wild-type and mutant genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ser 301 provides low resistance to the phenylpyrazole fipronil that does not impact the use of this insecticide in the field (9,43,46,47). However, fipronil-resistant strains isolated from two species of planthopper have been shown to contain an Ala to Asn, rather than Ser or Gly, mutation at the equivalent 301 site, found only in the heterozygous state (48,49). The lack of homozygous Asn individuals was proposed to be a result of lethality, supported by the reduced GABA median effective concentration (EC 50 ) observed in electrophysiological data (49).…”
mentioning
confidence: 99%
“…However, fipronil-resistant strains isolated from two species of planthopper have been shown to contain an Ala to Asn, rather than Ser or Gly, mutation at the equivalent 301 site, found only in the heterozygous state (48,49). The lack of homozygous Asn individuals was proposed to be a result of lethality, supported by the reduced GABA median effective concentration (EC 50 ) observed in electrophysiological data (49). Mutations resulting in lethality can only be viable in a heterozygous state, or more permanently, in a duplication of the type described in this study.…”
mentioning
confidence: 99%